2008
DOI: 10.1073/pnas.0807486105
|View full text |Cite
|
Sign up to set email alerts
|

A Schiff base connectivity switch in sensory rhodopsin signaling

Abstract: Sensory rhodopsin I (SRI) in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 53 publications
10
48
0
Order By: Relevance
“…7 Furthermore, as reported previously 7 and shown in Figure 5, the substitution of Ser for His166 inverts the SB deprotonation to the EC side. Therefore, an alternative proton acceptor exists.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…7 Furthermore, as reported previously 7 and shown in Figure 5, the substitution of Ser for His166 inverts the SB deprotonation to the EC side. Therefore, an alternative proton acceptor exists.…”
Section: Discussionsupporting
confidence: 70%
“…Similar measurements were used to calculate the charge shift ratio of the same mutants by Sineshchekov et al 7 to establish the charge movement inversion and suppression effect confirmed here.…”
Section: Resultssupporting
confidence: 60%
“…A similar inversion of protein function was previously observed in haloarchaeal sensory rhodopsin I (SRI), in which a single point mutation either of the photoreceptor itself or of its cognate transducer converted SRI from an attractant to a repellent photoreceptor (16,17). The SRI inversion is attributable to a switch in its conformation from the C (retinylidene Schiff base accessible from the cytoplasm) to E (Schiff base accessible from the extracellular space) conformer (18)(19)(20). The stable open channel of GtACR1_E68R is likely to be particularly valuable for structural comparisons with the WT by enabling identification of residue determinants and structural changes distinguishing the closed and open conformations of the channel by structural methods such as molecular spectroscopy and crystallography.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as the chemical shift value of the Pintermediate is significantly different from that of the Mintermediate, a rather large conformational change was observed, which may cause large changes in protein interactions, acting as a switch between positive and negative phototaxis functions. [16] After the P-intermediate was generated and trapped stationary under irradiation with 365 nm LED light of the Mintermediate, light illumination was stopped and the accumulation of the P-intermediate under dark conditions was observed (Figure 2 B). The signal intensity of the P-intermediate at 24.8 ppm decreased and that of the G-state at 13.8 ppm increased, indicating that the P-intermediate relaxed to the G-state.…”
mentioning
confidence: 99%